A study on electrospray mass spectrometry of fullerenol C60(OH)24 - Silion, Mihaela; Dascalu, Andrei; Pinteala, Mariana; Simionescu, Bogdan C.; Ungurenasu, Cezar (Beilstein Journal of Organic Chemistry, 2013)
Full characterization of fullerenol C60(OH)24 by HPLC ESI-MS in negative and positive ionization modes was achieved. Fragmentor voltage and capillary voltage were optimized in order to obtain a good signal stability and the best peak intensity distribution for the fullerenol C60(OH)24 in both negative and positive modes. While the predominant base peak observed for C60(OH)24 in the negative ionization mode was [M − H]− at m/z 1127, those observed in the positive mode were multiply charged [M − H2O + 4H]4+ at m/z 279 and [M − 12H2O + 2NH3 + 6H]6+ at m/z 158.
Keywords: electrospray; fullerenol C60(OH)24; mass spectrometry

(untitled) - Jin, H.; Chen, W. Q.; Tang, X. W.; Chiang, L. Y.; Yang, C. Y.; Schloss, J. V.; Wu, J. Y. (Neurosci. Res., 2000)

(untitled) - Gelderman, M. P.; Simakova, O.; Clogston, J. D.; Patri, A. K.; Siddiqui, S. F.; Vostal, A. C.; Simak, J. (Int. J. Nanomed., 2008)

(untitled) - Lu, L.-H.; Lee, Y.-T.; Chen, H.-W.; Chiang, L. Y.; Huang, H.-C. (Br. J. Pharmacol., 1998)

(untitled) - Silva, G. A. (Nat. Rev. Neurosci., 2006)

(untitled) - Silva, G. A. (Surg. Neurol., 2005)

(untitled) - Dugan, L. L.; Lovett, E. G.; Quick, K. L.; Lotharius, J.; Lin, T. T.; O’Malley, K. L. (Parkinsonism Rel. Disord., 2001)

(untitled) - Dugan, L. L.; Gabrielsen, J. K.; Yu, S. P.; Lin, T.-S.; Choi, D. W. (Neurobiology of Diseases., 1996)

(untitled) - Injac, R.; Radic, N.; Govedarica, B.; Perse, M.; Cerar, A.; Djordjevic, A.; Strukelj, B. (Pharmacol. Rep., 2009)

(untitled) - Injac, R.; Perse, M.; Cerne, M.; Potocnik, N.; Radic, N.; Govedarica, B.; Djordjevic, A.; Cerar, A.; Strukelj, B. (Biomaterials, 2009)

(untitled) - Injac, R.; Boskovic, M.; Perse, M.; Koprivec-Furlan, E.; Cerar, A.; Djordjevic, A.; Strukelj, B. (Pharmacol. Rep., 2008)

(untitled) - Chaudhuri, P.; Paraskar, A.; Sonii, S.; Mashelkar, R. A.; Sengupta, S. (ACS Nano, 2009)

(untitled) - Yin, J.-J.; Lao, F.; Meng, J.; Fu, P. P.; Zhao, Y.; Xing, G.; Gao, X.; Sun, B.; Wang, P. C.; Chen, C.; Liang, X.-J. (Mol. Pharmacol., 2008)

(untitled) - Zhu, J.; Ji, Z.; Wang, J.; Sun, R.; Zhang, X.; Gao, Y.; Sun, H.; Liu, Y.; Wang, Z.; Li, A. Q.; Ma, J.; Wang, T.; et al. (Small, 2008)

(untitled) - Pinteala, M.; Dascalu, A.; Ungurenasu, C. (Int. J. Nanomed., 2009)

(untitled) - Mrdanovic, J. Z.; Solajic, S. V.; Bogdanovic, V. V.; Djordjevic, A. N.; Bogdanovic, G. M.; Ijac, R. D.; Rakocevic, Z. L. J. (Dig. J. Nanomater. Biostruct., 2012)

(untitled) - Bogdanović, G.; Kojić, V.; Ðordević, A.; Canadanović-Brunet, J.; Vojinović-Miloradov, M.; Baltić, V. V. (Toxicol. in Vitro, 2004)

(untitled) - Chiang, L. Y.; Upasani, R. B.; Swirczewski, J. W.; Soled, S. (J. Am. Chem. Soc., 1993)

(untitled) - Schneider, N. S.; Darwish, A. D.; Kroto, H. W.; Taylor, R.; Walton, D. R. M. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Chiang, L. Y.; Upasani, R. B.; Swirczewski, J. W. (J. Am. Chem. Soc., 1992)

(untitled) - Husebo, L. O.; Sitharaman, B.; Furukawa, K.; Kato, T.; Wilson, L. J. (J. Am. Chem. Soc., 2004)

(untitled) - Singh, R.; Goswami, T. (J. Phys. Org. Chem., 2008)

(untitled) - Isaacson, C. W.; Kleber, M.; Field, J. A. (Environ. Sci. Technol., 2009)

(untitled) - Chao, T.-C.; Guixue, S.; Hansmeier, N.; Westerhoff, P.; Herckes, P.; Halden, R. U. (Anal. Chem., 2011)

(untitled) - Singh, R.; Goswami, T. (Thermochim. Acta, 2011)

(untitled) - Bobylev, A. G.; Kornev, A. B.; Bobyleva, L. G.; Shpagina, M. D.; Fadeeva, I. S.; Fadeev, R. S.; Deryabin, D. G.; Balzarini, J.; Troshin, P. A.; Podlubnay, Z. A. (Org. Biomol. Chem., 2011)

(untitled) - Kokubo, K.; Matsubayashi, K.; Tategaki, H.; Takada, H.; Oshima, T. (ACS Nano, 2008)

(untitled) - Kokubo, K.; Shirakawa, S.; Kobayashi, N.; Aoshima, H.; Oshima, T. (Nano Res., 2011)

(untitled) - Semenov, K. N.; Letenko, D. G.; Charykov, N. A.; Nikitin, V. A.; Matuzenko, M. Y.; Keskinov, V. A.; Postnov, V. N.; Kopyrin, A. A. (Russ. J. Appl. Chem., 2010)

(untitled) - Powell, W. H.; Cozzi, F.; Moss, G. P.; Thilgen, C.; Hwu, R. J.-R.; Yeryn, A. (Pure Appl. Chem., 2002)

(untitled) - Reeks, L. P.; Eichinger, P. C. H.; Bowie, J. H. (Rapid Commun. Mass Spectrom., 1993)

(untitled) - Morishetti, K. M.; Sripadi, P.; Mariappandar, V.; Ren, J. (Int. J. Mass Spectrom., 2011)

(untitled) - Mohan, H.; Palit, D. K.; Mittal, J. P.; Chiang, L. Y.; Asmus, K.-D.; Guldi, D. M. (J. Chem. Soc., Faraday Trans., 1998)

(untitled) - Mohan, H.; Chiang, L. Y.; Mittal, J. P. (Res. Chem. Intermed., 1997)

(untitled) - Arbogast, J. W.; Foote, C. S.; Kao, M. (J. Am. Chem. Soc., 1992)

(untitled) - Biczok, L.; Linschitz, H.; Walter, R. I. (Chem. Phys. Lett., 1992)

(untitled) - Stasko, A.; Brezova, V.; Biskupic, S.; Dinse, K.-P.; Schweitzer, P; Baumgarten, M. (J. Phys. Chem., 1995)

(untitled) - Dimitrijevic, N. M.; Kamat, P. V. (J. Phys. Chem., 1993)

(untitled) - Brezova, V.; Stasko, A.; Rapta, P.; Domschke, G.; Bartl, A.; Dunsch, L. (J. Phys. Chem., 1995)

(untitled) - Janaki, J.; Premila, M.; Goplan, P.; Sastry, V. S.; Sundar, C. S. (Thermochim. Acta, 2000)